2010
DOI: 10.5694/j.1326-5377.2010.tb03640.x
|View full text |Cite
|
Sign up to set email alerts
|

An education intervention for childhood asthma by Aboriginal and Torres Strait Islander health workers: a randomised controlled trial

Abstract: Objective: To assess the outcomes of an education intervention for childhood asthma conducted by Australian Indigenous health care workers (IHCWs). Design and setting: Randomised controlled trial in a primary health care setting on Thursday Island and Horn Island, and in Bamaga, Torres Strait region of northern Australia, April 2005 to March 2007. Participants: 88 children, aged 1–17 years, with asthma diagnosed by a respiratory physician (intervention group, 35; control group, 53; 98% Indigenous children). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…All the studies included in this review have important shortcomings that limit the reported findings. In previous studies conducted by members of our group using unadjusted values for spirometry, Indigenous children with lung disease (specifically asthma 38 and bronchiectasis 39 ) often had results within the healthy range for people of European ancestry. For example, the mean FEV 1 and FVC values in the asthma study were 95% predicted (SD, 18%) and 100% predicted (SD, 17%), respectively 38 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All the studies included in this review have important shortcomings that limit the reported findings. In previous studies conducted by members of our group using unadjusted values for spirometry, Indigenous children with lung disease (specifically asthma 38 and bronchiectasis 39 ) often had results within the healthy range for people of European ancestry. For example, the mean FEV 1 and FVC values in the asthma study were 95% predicted (SD, 18%) and 100% predicted (SD, 17%), respectively 38 .…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies conducted by members of our group using unadjusted values for spirometry, Indigenous children with lung disease (specifically asthma 38 and bronchiectasis 39 ) often had results within the healthy range for people of European ancestry. For example, the mean FEV 1 and FVC values in the asthma study were 95% predicted (SD, 18%) and 100% predicted (SD, 17%), respectively 38 . It is possible that a study that includes only healthy Indigenous Australians (strictly defined and with careful examination of medical history) will find spirometry reference values for Indigenous Australians similar to those for people of European ancestry, or requiring only a small adjustment factor.…”
Section: Discussionmentioning
confidence: 91%
“…Rarely have the views of uses of the service been evaluated. Having documented the positive asthma outcomes of the education intervention program, we sought to obtain parents'/carers' perspective of the service model used so as to characterise the aspects of a clinical service model that lead to improved health outcomes from a community perspective. The seven themes generated from the parents'/carers' perspective relate to the cultural aspects (established rapport/caregiver satisfaction, local‐based approaches with involvement of HCW) and the high level of expertise in content and local issues (clear communication, quality service delivery, professional approach, clear transfer of education).…”
Section: Discussionmentioning
confidence: 99%
“…The health worker conducting the 12‐month follow‐up interview was not the same IHCW who provided the additional education sessions, and the doctors were not present when the interview took place. Results for the intervention study have been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation